Emotion, ritual and power in Europe, 1200-1920 : family, state and church - Bailey, Merridee L.; Barclay, Katie ca. 20./21. Jahrhundert (Palgrave Studies in the history of emotions, 2017)
This edited collection applies a new methodology to a study of the relationship between ritual, emotion and power. In doing so, it provides access to cutting-edge research and approaches on this theme and rejuvenates an older topic of interest to both historians and anthropologists, establishing new questions and a new approach for scholarship in the twenty-first century. The relationship between ritual and the creation, maintenance and destabilisation of power has not gone unexplored given the centrality of ritual to religious practice and to institutional structures, yet the place emotion plays in the relationship between ritual and power has received less attention, particularly in historical context. This collection explores the nature of these relationships, seeking to better understand how emotions act within ritual to inform balances of power.0The editors are particularly interested in the ways that rituals and emotions are situated in and change over time, and the ways that rituals, emotions and power have been implicated in processes of change and continuity